PENGARUH BRIEF COUNSELING TERHADAP KADAR GULA DARAH PASIEN DIABETES MELITUS TIPE 2 DI RSUD DR. H. MOCH. ANSARI SALEH BANJARMASIN - Muhammad Reza Pahlevi; Abdul Rahem; Valentina Metasartika; Riza Alfian (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2018)
Diabetes mellitus is one of the chronic diseases characterized by blood sugar levels above normal values. Blood sugar levels are not controlled can develop into diseases such as heart disease, kidney failure, and stroke. Diabetes mellitus patients require intervention from pharmacists to achieve the outcome of therapy in the form of controlling blood sugar levels within normal limits. The purpose of this study was to determine the effect of briefing counseling on blood sugar levels of diabetes mellitus type 2 in patients at Dr. H. Moch. Ansari pious Banjarmasin. This study used a randomized controlled trial design. A total of 156 samples were divided into two randomized groups of 78 patients receiving the intervention (treatment group) and 78 patients not receiving intervention (control group). Intervention method was a brief counseling. Exclusion criteria in this study were patients with deaf, illiterate and uncooperative conditions. Blood sugar data collected were fasting blood sugar levels taken from the patient's medical records. Blood sugar data were analyzed by wilcoxon and mann whitney test. The results showed that there was a significant decrease in fasting blood glucose level in post-study in both groups (p<0.05). Differences in fasting blood glucose levels between the two groups did not have a significant difference (p=0.16). The value of decrease of fasting blood glucose level of control group and treatment group were 16.32 ± 11.56 mg/dL and 16.87 ± 27.88 mg/dL respectively. The conclusion of this study is the decrease in fasting blood sugar levels of diabetes mellitus patients who were given either brief interval counseling or who were not given intervention had no difference.